2021
DOI: 10.1038/s41598-021-95426-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance training on gait velocity and knee adduction moment in knee osteoarthritis patients: a systematic review and meta-analysis

Abstract: The systematic review aimed to analyze the effects of resistance training in knee osteoarthritis (OA) rehabilitation from a biomechanical perspective. A meta-analysis was performed to determine the potential benefits of resistance training on patients with knee OA. Relevant studies based on the inclusion and exclusion criteria were selected from CENTRAL, PubMed, Scopus, and Web of Science databases inception to August 2020. Outcome measures included gait velocity and knee adduction moment (KAM). The mean diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
1
7
1
Order By: Relevance
“…The present study also showed that walking exercises improved pain-related behaviors, OA symptoms, inflammation status, and weight loss to decrease body fat more and muscle mass less. On the other hand, a systematic review showed that resistance training enhances the gait velocity in patients with knee OA but not knee adduction moment [38]. Furthermore, the present study showed that walking exercise reduced proinflammatory cytokine expression in the articular cartilage and the morphology of the knee joint in MIA-induced knee OA.…”
Section: Discussionsupporting
confidence: 43%
“…The present study also showed that walking exercises improved pain-related behaviors, OA symptoms, inflammation status, and weight loss to decrease body fat more and muscle mass less. On the other hand, a systematic review showed that resistance training enhances the gait velocity in patients with knee OA but not knee adduction moment [38]. Furthermore, the present study showed that walking exercise reduced proinflammatory cytokine expression in the articular cartilage and the morphology of the knee joint in MIA-induced knee OA.…”
Section: Discussionsupporting
confidence: 43%
“…Interestingly, the first peak KAM did not increase with walking speed after exercise therapy; conversely, a previous systematic review suggested that walking speed affected the amplitude of joint moment in patients with knee OA, as well as in different populations 51 . Considering results from our regression analysis and a previous systematic review that suggested resistance training would enhance walking speed, but not KAM, in patients with knee OA 9 , it may be suggested that patients with knee OA demonstrate an increase in the first peak KAM through different pathways than the increase in the first peak KAM owing to an increase in walking speed. Other potential mediators, such as pain improvement, also increased the first peak KAM.…”
Section: Discussionmentioning
confidence: 62%
“…The specific search strategies are shown in the Supplementary Method. Google Scholar functioned as a complementary search engine, and a manual search of the reference lists of previous systematic reviews 8,9 was also performed. After excluding duplicate studies, two reviewers (MY and HI) independently evaluated all titles and abstracts to determine whether they would be eligible for subsequent full-text review.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease of 2 points in the pain score and a decrease of 9.1 scores in the function subscale of the WOMAC questionnaire are examples of clinically relevant improvement [ 47 , 49 , 50 ]. A mere 5% change in KAM was shown to improve OA symptoms [ 51 , 52 ] which will be considered as a clinically relevant improvement of the KAM in this trial. The results from this trial will provide vital evidence on clinical and biomechanical outcomes following OKC and CKC exercise programs in people with mild knee OA.…”
Section: Discussionmentioning
confidence: 99%